Problems in The Advertising Tax Collection Process at The Regional Revenue Agency Of Surabaya City: A Qualitative Descriptive Study: Permasalahan Dalam Proses Penagihan Pajak Reklame Pada Badan Pendapatan Daerah Kota Surabaya: Studi Deskriptif Kualitatif - Trista Pramudiya, Nanda; Priana Primandhana, Wiwin; Sishadiyati, Sishadiyati (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
Advertising tax is a crucial component in increasing Regional Original Revenue (PAD), especially in large cities like Surabaya. However, its implementation at the Surabaya City Regional Revenue Agency (Bapenda) still faces various obstacles that impact low tax revenue realization. These problems include a lack of oversight of illegal advertising, weak collection follow-up, and low taxpayer awareness and compliance. This study aims to identify key issues in the advertising tax collection process and formulate relevant and applicable solutions. This study used a qualitative descriptive approach, with data collection techniques including field observations, semi-structured interviews with tax officials and taxpayers, and supporting documentation. The results identified six main factors hindering collection: (1) minimal outreach, (2) a suboptimal administrative system, (3) weak law enforcement, (4) limited human resources, (5) negative public perception, and (6) data disintegration. The implications of this research are the importance of tax system reform, strengthening inter-agency coordination, and increasing institutional capacity through training and more effective and sustainable public information communication strategies.